(untitled) (Research, Society and Development, 2020)
Academic monitoring is a teaching and learning modality that may be part of the student’s training process, integrating research and extension activities. That training may be assisted with the use of active methodologies, contributing to a more dynamic and integrative teaching. Thus, it is intended to report the experience of monitoring with different approaches of active methodologies, in order to show the importance of the learning process construction in the discipline of Physiology to the Physical Education course. The aspects involved with the experience show the active methodologies applications in the discipline and their contributions in this teaching-learning process. Those applications were fundamental to increase the academic success of the students, since the problematizations, creativity, autonomy and criticisms stimulated by the application of these methodologies, favored a better understanding and comprehension of the content by the student. Therefore, it has been found that the participation of the monitor in the application of active methodologies in the discipline of Physiology was important in the academic education of all those involved. Both students and monitors were encouraged to explore subjects studied in Physiology, in a critical and autonomous way, contributing to the teaching-learning process of the student/monitor/teacher triad.